A Treatment Protocol of Jwara in the Perspective of examination of Kala (Time) - Kumar, Vipin; Verma, Sheetal (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda Jwara is not merely the concept of raised body temperature but it is a disease having “Deha- Indriya Manah Santap” as a cardinal characteristic. This can be understood as the state where body, mind as well as sense organs suffer due to high temperature. Jwara is regarded superior among all the diseases and hence detailed explanation of this disease is available in Ayurvedic literature. Aam is the main factor initiating Jwara. Hence Langhana therapy has been referred as the first step in treatment in Jwara. Various treatment modalities have been described in Jwara Chikitsa like Langhana, Svedana, Kala, Yavagu, Tikta Rasa, Pachana, Ghritpana, Virechana, Dugdhapana etc. Application of all these procedures will yield favourable results only if while following Chikitsa krama (sequence) Kala factor is assessed properly. Kala is broadly classified as Nityaga and Avastika. Avastika Kala signifies the state of disease for drug administration. Treatment of such an important disease should be understood clearly. Here an attempt has been made to elaborate and simplify Chikitsa sutra and Chikitsa Krama of Jwara in relation to Avastika Kala.